An overview of Stuart Hall’s encoding and decoding theory with film communication - Yuting, Xie; Yasin, Megat Al Imran; Shekh Alsagoff, Syed Agil; Lay, Hoon Ang (Caddo Gap Press, 2022)
British scholar Stuart Hall is the father of contemporary cultural studies, as well as one of the media and cultural theorists and critics. His famous theory of “encoding and decoding” (1973) plays a significant role in film and television studies. This research reviewed related literature about this theory and combined it into the study of film communication to analyze. According to the summary, this research found that Hall’s “encoding and decoding” theory can be utilized in the studies of film communication, including the studies of the type of adapted films. It helps to comprehend that film as a sort of meaningful discourse, its richness became one of the reasons that form the complexity of both the communication process and audience reception. Importantly, in terms of such application, the theory can help to understand the specific dissemination process and various interpretations of different audiences’ decoding positions in this process. The purpose of this research is to make people better comprehend the film communication process that involves related objects, offering an angle for scholars and practitioners to explore the reception of film audiences based on Hall’s theory.